Thematic Choices in Chimamanda Ngozi Adichie’s Discourse: We Should All Be Feminists - Issa Djimet (Mediterranean Journal of Social Sciences, 2022)
This paper is about the analysis of Chimamanda’s discourse on feminism. The paper adopts the systemic functional approach to language, notably the textual meaning so as to find out what are the thematic choices made by the author of the discourse and how this contributes in constructing or deconstructing cultural beliefs about women. The linguistics data are analyzed both on the quantitative and qualitative bases, that is, the paper uses the mixed research method. The discourse is therefore split into analyzable units referred to as clauses to which figures and statistics are meticulously ascribed. The results reveal a predominance of Topical Themes followed by textual ones whereas interpersonal elements are rarely thematized in the discourse. Furthermore, the analysis discloses a significant number of marked Themes. It is through such thematic choices that the author highlights and deconstructs discriminating prejudices by emphasizing positive attitudes that might bring about cultural changes in favor of women’s empowerment. Received: 26 April 2022 / Accepted: 30 June 2022 / Published: 5 July 2022